Pengaruh Pendapatan Sewa Modal, Jumlah Nasabah dan Kredit yang Diberikan terhadap Perolehan Laba Bersih PT Pegadaian Persero Indonesia Periode 2008-2022 - Mauludi, Ali; Difani A’isyah Fitri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to provide empirical evidence by examining the influence of rental income, the number of customers, and loans granted on the profitability of PT Pegadaian Indonesia. sing an associative, quantitative approach, the study analyzes 15 annual financial reports from 2008 to 2022, and samples were drawn using a saturated sampling technique. Sourced from PT Pegadaian's official website at https://www.pegadaian.co.id/. The data analysis technique employed is multiple linear regression. The research findings indicate the following: 1. Rental income has a significant positive effect on the net profit of PT Pegadaian Persero Indonesia, as evidenced by a t-statistic probability value of 0.015 < 0.05, thus accepting the researcher's hypothesis H1. 2. The number of customers does not have a significant effect on the net profit of PT Pegadaian Persero Indonesia, as indicated by a t-statistic probability value of 0.305 > 0.05, leading to the rejection of the researcher's hypothesis H2. 3. Loans granted show a significant positive effect on the net profit of PT Pegadaian Persero Indonesia, with a t-statistic probability value of 0.040 < 0.05, thereby accepting the researcher's hypothesis H3. 4. Rental income, the number of customers, and loans granted simultaneously have a significant positive effect on the net profit of PT Pegadaian Persero Indonesia, as indicated by an F-statistic value of 30.26915 with a Prob(F-Statistic) value of 0.000013 < 0.05, thus accepting the researcher's hypothesis H4. In conclusion, rental income and loans granted can partially influence net profit, while the number of customers does not. However, when considered together, all three variables significantly impact net profit.